(untitled) (Cambridge, UK, 2002)
The book discusses various approaches for minimizing undesirable changes, such as High Temperature Short Time techniques and new thermal technologies and reviews the range of thermal technologies such as infrared heating, dielectric methods, and ohmic heating (Editorial Reviews)
Các kỹ thuật chế biến thực phẩm hiện đại
Keywords: Food industry and trade